The effect of pretreatment with casein phosphpeptide and fluoride on the shear bond strength of orthodontic bonding - Tabrizi, Anis (My University, 2007)
﻿ ﻿ Özet Bu çalısmanın amacı, mineye sadece flor, sadece kazein fosfopeptit ve kazein fosfopeptitle beraber flor uygulamasıyla yapıstırılmıs ortodontik braketlerin çıkarılması sırasındaki hataları ve kopma direncini incelemektir. Çalısma seksen adet saglam küçük azı disi kullanılarak gerçeklestirilmistir. Bütün disler, alçı tabanına dik gelecek ve bukkal yüzleri açık bırakılacak sekilde akrilik rezin içerisine yerlestirilmistir. Her bir grup, yirmi dis içerecek sekilde, disler rastgele dört esit gruba bölünmüstür. Hlk grup, kontrol grubu olarak adlandırılmıstır. Hkinci gruba, profilaktik flor cilası olan Duraphat (Duraphat Colgate Oral Pharmaceuticals, Inc., Canton, Mass) uygulanmıstır. Üçüncü gruba sadece kazein fosfopeptit (KFP) (MI Paste PROSPEC Recaldent G.C. Tooth Mouse) uygulanırken, dördüncü gruba hem flor cilası hem de kazein fosfopeptit uygulanmıstır. Bondinge hazırlanırken, her disin bukkal yüzü asitlenmistir. Dislerin üzerine bonding adeziv kompozit, ortodontik metal braketleri yapıstırmak amacıyla uygulanmıs ve 40 saniye boyunca polimerize edilmistir. Bondun kopma testi için, kuvveti ileten kısa ve kalın bir aparat (Ultradent) 1 mm/ dk hız ile, her örnek disin dis ile kompozit arasına, kopma meydana gelene dek uygulanmıstır. Kopma direnci, ANOVA degisken analizi ile istatistiksel olarak ölçülmüstür. Debonding islemi sonrasında mine yüzeyinde kalan artık adezivler, ARI(Adhesive Remnan Index) ile ölçülmüstür. Kopma degerleri kontrol grubu, flor uygulanan grup, kalsiyum uygulanan grup ve hem kalsiyum hem de flor uygulanan grup için sırasıyla 21.02±5.24 MPa, 14.02±4.64 MPa, 22.57±4.32 MPa ve 21.69±3.57 Mpa olarak bulunmustur. Tukey HSD test sonuçları kopma kuvvetlerinin, kontrol grubu, kalsiyum uygulanan grup ve hem kalsiyum hem de flor uygulanan grup arasında istatistiksel olarak anlamlı bir fark göstermedigini ancak flor uygulanan grupda kopma kuvvetlerinin anlamlı olarak azaldıgını ve ANOVA (P<0.001) göstermistir. Tüm gruplarda en fazla ayrılma braket-rezin arayüzünde meydana gelmistir. Hiçbir grubun ARI sonuçları arasında anlamlı bir fark bulunmamıstır. (P<0.426) Bu çalısmanın sonuçları göstermistir ki, ortodontik braketten önce flor uygulaması istatistiksel olarak anlamlı bir fark meydana getirmisse de kazein uygulamasının böyle bir etkisi olmamıstır. Flor, Kazein, Ortodontik Braketler, Kopma Direnci,Kalan yapistirici. The aim of this study was to investigate the shear bond strength (SBS) and debonding failure modes of orthodontic brackets which will be bonded to enamel following the application of fluoride only, casein phosphopeptide only and fluoride together with casein phosphopeptide. Eighty extracted sound human premolar teeth were used in this study. All teeth were mounted in acrylic resin leaving the buccal surface of the crowns vertical to the base of the moulds. Teeth were randomly divided into four equal groups each contained twenty teeth. First group of teeth served as the control group. Second group was treated with prophylaxis fluoride varnish Duraphat (Duraphat Colgate Oral Pharmaceuticals, Inc., Canton, Mass.). Third group was treated with casein phosphopeptide (CPP) (MI Paste PROSPEC Recaldent G.C. Tooth Mousse) only and fourth group was treated with casein phosphopeptide along with fluoride varnish. In preparation for bonding, the buccal enamel of each tooth was etched. Bonding adhesive composite (Light Bond and Composite, Reliance), was used to bond metal orthodontic brackets to each tooth and was cured for 40 seconds. For shear bond testing, a stubby-shape force transducer apparatus (Ultradent) was applied at a cross head speed of 1 mm/ minute to each specimen at the interface between the tooth and composite until failure occurred. The SBS data was statistically evaluated using analysis of variance (ANOVA). The residual adhesive on the enamel surface following debonding were evaluated using the Adhesive Remnant Index (ARI). The results revealed that the SBS values were 21.02 ± 5.24 MPa, 14.02±4.64 MPa, 22.57±4.32 MPa and 21.69±3.57 MPa for control, treated with fluoride, treated with calcium, and treated with fluoride and calcium groups, respectively. The results of the Tukey HSD test showed that there were no statistically significant differences among groups control, treated with calcium and treated with both calcium and fluoride. While the group treated with fluoride yielded significantly lower S.B.S values and ANOVA was showen to be (P<0.001). The most frequent debonding distribution occurred in the tooth resin interface. There was no statistical difference between any of the groups’ ARI scores (P< 0.426). The results of this study suggest that although the use fluoride prior to orthodontic bracket bonding showed statistically significant differences in the shear bond strength, all the values were still clinically acceptable. Key Words: Fluoride, casein, Orthodontic brackets, Shear bond strength, Residual adhesive.
Keywords: Ağız ve Diş Sağlığı; Ortodonti